Hydrogen sulfide mediated alleviation of cadmium toxicity in Phlox paniculata L. and establishment of a comprehensive evaluation model for corresponding strategy. Issue 10 (23rd August 2020) - Wang, Hong-Rui; Che, Yan-Hui; Huang, Dan; Ao, Hong
Abstract: A laboratory experiment was performed to evaluate the potential role of H2 S on cadmium (Cd) toxicity in Phlox paniculata L. Seeds pretreated with 0.3, 0.6, 0.9, and 1.2 mM NaHS as a donor of H2 S for 24 h and subsequently exposed to 100, 200, and 300 μM CdCl2 for 26 days had significantly higher germination rate compared with Cd alone. Meanwhile, 2-year-old seedlings sprayed with 0.3, 0.6, and 0.9 μM NaHS were grown in soil with 0.3, 0.6, and 1.2 mg/kg CdCl2, respectively. We observed that H2 S decreased Cd accumulation in leaves and elevated Cd concentration in roots. Cd toxicity in seedlings resulted in a substantial increase in Cd-induced overproduction of malondialdehyde (MDA), Cd accumulation, and electrolyte leakage. Meanwhile, addition of NaHS increased photosynthetic performance compared with Cd alone. Exogenous H2 S significantly elevated biomass, improved antioxidant enzyme activities, and reduced ABA content compared with Cd alone. H2 S also plays an important role in the ABA signaling pathway during stress. Notably, NaHS promoted Cd uptake by Phlox paniculate L. from soil. The prediction model of H2 S for increasing plant resistance and reducing soil Cd pollution was established by factor analysis method based on comprehensive evaluation of plant stress physiology.